Recent progress of bioinspired cartilage hydrogel lubrication materials. Issue 3 (2nd September 2022) - Zhao, Xiaoduo; Zhao, Weiyi; Zhang, Yunlei; Zhang, Xiaoqing; Ma, Zhengfeng; Wang, Rui; Wei, Qiangbing; Ma, Shuanhong; Zhou, Feng
Abstract: Hydrogels have been considered as potential candidates for cartilage replacement due to their high‐water content, extreme network hydration, excellent biocompatibility and tunable mechanical properties. Currently, the development of high‐performance cartilage‐inspired hydrogel lubrication materials has become a hot topic in the field of biomedical materials. This review focusses on the recent development of cartilage‐inspired high‐strength hydrogels from the viewpoints of bionic surface/interface and biotribology. Specifically, the composition structure and extraordinary lubrication mechanism of the natural articular cartilage are overviewed first. Subsequently, some of the novel biomimetic design strategies for preparing high strength cartilage hydrogels with various network structures are summarised in detail, while systematic evaluation of lubrication properties and mechanisms are discussed. Furthermore, new surface modification means for improving the lubrication feature of high strength cartilage hydrogel materials are presented. In addition, in order to demonstrate the application potential of cartilage hydrogels in clinical, several bonding methods to decorate hydrogels onto surfaces of natural bone tissues or artificial joint materials are introduced. Finally, current challenges and future research directions are discussed for cartilage‐inspired hydrogel lubrication materials.